2013
DOI: 10.1021/jf4019855
|View full text |Cite
|
Sign up to set email alerts
|

Processing Technologies and Cell Wall Degrading Enzymes To Improve Nutritional Value of Dried Distillers Grain with Solubles for Animal Feed: an in Vitro Digestion Study

Abstract: Currently, the use of maize dried distillers grain with solubles (DDGS) as protein source in animal feed is limited by the inferior protein quality and high levels of non-starch polysaccharides (NSP). Processing technologies and enzymes that increase NSP degradability might improve digestive utilization of DDGS, enhancing its potential as a source of nutrients for animals. The effects of various combinations of processing technologies and commercial enzyme mixtures on in vitro digestion and subsequent fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…The observed correlation of DFAs to insoluble galactose is in line with previous studies describing highly complex feruloylated heteroxylan side chains containing up to two galactose residues from corn bran. 24,25 The observed greater content of DFAs in DDGS from P1 is likely related to the higher content of insoluble arabinoxylan in DDGS from P1 than from P2−P5, as reported by Pedersen et al 2 The simultaneous sampling of both corn grains and corresponding DDGS over 11 months allowed for investigating 26,27 Overall, the analysis of corn and DDGS indicated that the individual composition of DFAs and TriFAs is conserved, indicating that DFAs and TriFAs are basically not modified during ethanol fermentation and subsequent drying of DDGS. Previous characterization of NSP profiles of the samples led to the hypothesis that only arabinoxylan from corn endosperm, which comprises only a minor fraction of the total arabinoxylan, was modified during DDGS production.…”
Section: ■ Discussionmentioning
confidence: 73%
“…The observed correlation of DFAs to insoluble galactose is in line with previous studies describing highly complex feruloylated heteroxylan side chains containing up to two galactose residues from corn bran. 24,25 The observed greater content of DFAs in DDGS from P1 is likely related to the higher content of insoluble arabinoxylan in DDGS from P1 than from P2−P5, as reported by Pedersen et al 2 The simultaneous sampling of both corn grains and corresponding DDGS over 11 months allowed for investigating 26,27 Overall, the analysis of corn and DDGS indicated that the individual composition of DFAs and TriFAs is conserved, indicating that DFAs and TriFAs are basically not modified during ethanol fermentation and subsequent drying of DDGS. Previous characterization of NSP profiles of the samples led to the hypothesis that only arabinoxylan from corn endosperm, which comprises only a minor fraction of the total arabinoxylan, was modified during DDGS production.…”
Section: ■ Discussionmentioning
confidence: 73%
“…Four nutritional characteristics, i. e., dry matter digestibility, protein digestibility, digestible amino‐acid content, and amino‐acid digestibility were calculated using the following equations, which were derived from Vries et al (): Dry0.25emmatter digestibility,%=Dry0.25emmatter content in supernatant after0.25emitalicin vitro0.25emdigestion,normalgDry0.25emmatter content in DDGS before0.25emitalicin vitro0.25emdigestion,normalg×100% Protein digestibility,%=Protein content in supernatant after0.25emitalicin vitro0.25emdigestion,normalgProtein content in DDGS before0.25emitalicin vitro0.25emdigestion,normalg0.25em×100% lefttrueDigestible aminoacid content,mnormalg1lysineasexample=Lysine content in DDGS,mnormalg1Lysine content in residue afterin vitrodigestion,mgWeight of DDGS beforein vitrodigestion,g Aminoacid digestibility,%()lysine0.25emas0.25emexample=Digestible Lysine content after0.25emitalicin vitro0.25emdigestion,mgTotal Lysine content in DDGS before0.25emitalicin vitro0.25emdigestion,mg×100%. …”
Section: Methodsmentioning
confidence: 99%
“…Wet-milling of maize dried distillers grains with solubles increased in vitro crude protein digestibility (113) . It is possible, as suggested by these authors, that the disruption of the cell wall structure leads to increased enzyme accessibility and that the improved in vitro digestion is not linked directly to changes in protein structure, although the latter point was not measured by the authors.…”
Section: Particle Size Reduction Processingmentioning
confidence: 96%